Family rearrangements arising from the mother's imprisonment and impact on the system family - Ortiz Aguilar, Leticia (Facultad de Trabajo Social y Desarrollo Humano, 2022)
As is well known, the phenomenon of women in prison has had an exponential growth, with the state of Chihuahua having shown the highest growth in the prison population nationwide in past decades; women enter the ranks of crime more and more every day, either because of a lack of job opportunities that allow them to meet the economic needs of their family or because they are influenced and sometimes forced by their partners, in addition to the fact that the issue of the psycho-emotional state presented by the family system due to the family adjustments arising from the mother’s entry into prison and the abandonment of the father has been little studied, together with the inequality that arises in the application of laws and penalties for men and women, the latter being the most affected with little-explored social, emotional and family consequences. This document aims to report part of the results obtained from the research work carried out at the State Social Reintegration Center number 2 in Ciudad Juárez, Chihuahua Mexico. The objective was to confirm whether the reorganization and family restructuring that occurs in these systems causes minors to occupy roles that do not correspond to them, losing their sense of belonging to their peers and presenting behaviors that threaten their emotional and social integrity, emphasizing the emotions, feelings and behaviors presented by mothers, caregivers and minors who are left adrift. Some of the findings were that the families studied generated movements within the system modifying the reorganization and family dynamics and the execution of parental tasks, presenting in specific two-family typologies more frequently. Regarding the effects that occurred, they were related to physical and emotional health, economic and social mainly.